TemporalContext-2021-FinWhale - Madhusudhana, Shyam; Yu Shiu; Klinck, Holger; Fleishman, Erica; Liu, Xiaobai; Nosal, Eva-Marie; Helble, Tyler; Cholewiak, Danielle; Gillespie, Douglas; Širović, Ana; Roch, Marie (Zenodo, 2021)
This dataset contains representative fin whale (Balaenoptera physalus) acoustic data and annotations to train recognition models using code available at https://github.com/shyamblast/TemporalContext-2021 We thank staff of NOAA Channel Islands National Marine Sanctuary for their support of data collection as well as the teams of the Scripps Institution of Oceanography - Marine Bioacoustics Research Collaborative for their dedicated work building, deploying, and processing instrumentation and data used in this paper.